The Role of Syntactic Stylistic Means in Expressing the Emotion Term Love - Panasenko, Nataliya (Research in Language, 2013)
Love as one of important feelings in human emotional, cognitive and social life has always attracted attention of the researchers: psychologists, linguists, philosophers, ethnologists, etc. We may speak about extralinguistic and linguistic ways of love manifestation. To linguistic ones belong, of course, stylistic means, which include lexical, syntactic, phonetic, and semasiological level. The author focuses on lexical-syntactical means of expressing love in two Slavic languages, Czech and Slovak, using linguocognitive and cultural approach. This research is inspired by the GRID project, which aimed at study of 24 emotion terms in 35 languages.